Kolaborasi antara Pemerintah Provinsi Daerah Istimewa Yogyakarta dan Kalurahan dalam Penggunaan Dana Keistimewaan - Analius Giawa; Rukoyah Rukoyah (LP2M Universitas Sarjanawiyata Tamansiswa, 2024)
Provilege fund is matter that attached to the Province of Yogyakarta Special District as a special autonomous region. The privilege fund has an objective to create prosperity for the socieites of the through the benefit optimalization of each activity done and relevant with the special authority. The Use of Privilege Fund cannot be separated from the synergic collaboration among stakeholders that in this analysis focuses on the Collaboration between Province Government Of the Special Region Of Yogyakarta And Kalurahan Government In in the use of privilege fund. This issue becomes a special attention because the high poverty condition level in DIY, which is based in the village areas. The intertwined collaboration between province. Government Of the Special Region Of Yogyakarta And Kalurahan Government In in the use of privilege fund generally becomes an instrument to increase the rate of economic growth and Yogyakarta societies’ welfare. This research utilized Qualitative Method with phenomenology approach. The data collection technique was performed through observation, interview and documentation. This analysis result indicates that the collaboration built between province and Kalurahan government (village) has not been holistically correlated so that the relation is more hierarchic (top down). Besides, there is an ambiguity tendency towards the spirit of villages to build that causes the low local initiatives and generally the authority possessed by the villages.